Unraveling communication between child patients’ family members and healthcare staff - Deddy Mulyana; Devie Rahmawati; Hermito Gidion; Elsa Roselina (Universitas Padjadjaran, 2021)
Health Communication in general and therapeutic communication in particular as relatively new communication fields are getting more important at the present, let alone in Indonesia with a population of over 270 million people. They come from hundreds of ethnic groups that may have different assumptions about the causes of and the solutions to various diseases and illnesses. Many health problems are related to communication problems between health providers and patients who may come from different cultures. These communication problems occasionally lead to medical malpractice. It is based on this reason that effective communication between healthcare staff (doctors and nurses) and patients (and their families) is deemed critical in bringing about satisfying results for both parties. This study aims to unravel therapeutic communication between healthcare staff and family members of patients. It used a phenomenological qualitative research method. The sample of the study were family members of child patients hospitalized in two hospitals in Jakarta who accompanied the child patients during their hospitalization from 2015 to 2017 and in 2019. The sample consisted of 30 participants; they all were interviewed and observed in the study. Without aiming to make generalizations, the research findings showed that in essence the research participants were satisfied with the communication conducted by the healthcare staff and the BPJS (Badan Penyelenggara Jaminan Sosial or Social Security Administrator) program provided by the Government. But some of them had their unspoken dissatisfaction with the overall treatment process related to doctors’ communication and the deficiency of the BPJS program.